Utilization of Audiovisual Media as an Effort to Prevent CED and Anemia in Pregnancy - Septalia Isharyanti, Septalia Isharyanti (Poltekkes Kemenkes Medan, 2024)
Women of reproductive age as expectant mother would pay attention to their nutritional status. Balanced nutrition during pregnancy must been prepared from the pre-conception period. Lack of nutritional intake during pregnancy had a negative impact on both the mother and baby. One of the nutritional problems in pregnant women was Chronic Energy Deficiency (CED) and anemia. Efforts to reduce the incidence of CED and anemia in pregnancy by providing health education regarding balanced nutritional intake during the pre-conception period. The use of audiovisual media was an option for providing education to the public, because it was considered easier to remember and understand. Research purpose was to determine the effectiveness of using audiovisual media on the level of knowledge, attitudes and motivation in women of reproductive age in preventing CED and anemia in pregnancy. The method was quasi-experiment using a pre-post test design with control group. The study was divided into 2 groups, the treatment group was given health education by using audiovisual media and the control group was given health education using flipchart media. The treatment group consisted of 18 samples, the control group consisted of 19 samples. Data were collected before and after being given health education to determine the level of knowledge, attitudes and motivation of women of childbearing age in preventing of CED and anemia in pregnancy using a questionnaire. The result showed there was a difference in knowledge before and after being given health education using both audiovisual media and flip sheets with a p value for both groups of 0.005. There was no difference in attitudes and motivation before and after being given health education using either audiovisual media or flip sheets with a p value > 0.05. The difference test between the two groups showed no significant differences in the use of audiovisual media and flip sheet media with a p value for each knowledge, attitude and motivation variable > 0.05.